Study on the material compatibility of 2-bromo-3, 3, 3-trifluoropropene with the polymers used in built-in fire extinguishing system of aircraft. (December 2022) - Bai, Huilin; Huang, Xin; Yuan, Wei; Zhou, Xiaomeng
Highlights: Material compatibility analysis between a new fire extinguishing agent and typical elastomer sealing materials. In depth theoretical analysis of the damage mechanisms for agent-polymer interaction. This is beneficial to the material selection of fire extinguishing system. Abstract: The seals are usually used to fill the gap between the storage containers and discharge pipes in the built-in fire extinguishing system of the aircraft. These seals inevitably touch the fire extinguishing agents, which may reduce the hermeticity of seals. In this paper, the compatibility experiment of 2-bromo-3, 3, 3-trifluoropropene, a new clean fire extinguishing agent, with fluorosilicone rubber and fluoro rubber was performed at 25 ℃, 0.1Mpa. The volume, weight, hardness, and mechanical properties of the sealings were tested, and the changes in cross-section and infrared spectrum were analyzed. The results show that during the contact with 2-bromo-3, 3, 3-trifluoropropene, fluoro rubber is damaged more severely than fluorosilicone rubber, the hardness measured directly and after drying decreased by 12.9 % and 17.6 % respectively, while the tensile strength decreased by 51.2 % and 86.1 % respectively. It is proved that 2-bromo-3, 3, 3-trifluoropropene have poor compatibility with the fluoro rubber and fluorosilicone rubber.